Spontaneous resolution rates of vesicoureteral reflux in Brazilian children: A 30-year experience - Filho, Miguel Zerati [UNESP]; Calado, Adriano A. [UNESP]; Barroso Jr., Ubirajara [UNESP]; Amaro, João Luiz [UNESP] (FapUNIFESP (SciELO), 2007)
Objective: We evaluated clinical characteristics of primary vesicoureteral reflux (VLJR) in infants in a 30-year period in Brazil with special reference to the relation of renal parenchymal damage to urinary tract infection and gender. Materials and Methods: From 1975 through 2005, 417 girls (81.6%) and 94 boys (18.4%) with all grades of reflux were retrospectively reviewed. Patients were categorized by the worst grade of reflux, maintained on antibiotic prophylaxis and underwent yearly voiding cystourethrography until the reflux was resolved. VUR was considered resolved when a follow-up cystogram demonstrated no reflux. Surgical correction was recommended for those who fail medical therapy, severe renal scarring or persistent VUR. Results: Grades I to V VUR resolved in 87.5%, 77.6%, 52.8%, 12.2% and 4.3%, respectively. Renal scars were present at presentation in 98 patients (19.2%). Neither gender nor bilaterality versus unilaterality was a helpful predictor of resolution. The significant difference was found among the curves using the log rank (p < 0.001) or Wilcoxon (p < 0.001) test. Conclusion: Despite the current use of screening prenatal ultrasound, many infants are still diagnosed as having vesicoureteral reflux only after the occurrence of urinary tract infection in our country. Scarring may be associated to any reflux grade and it may be initially diagnosed at any age but half of the scars are noted with higher grades of reflux (IV and V). The incidence of reflux related morbidity in children has significantly diminished over the last three decades.
Keywords: Reconstructive surgical procedures; Ureter; Vesico-ureteral reflux; antibiotic prophylaxis; child; female; follow up; hospitalization; human; infant; kidney; male; pathology; pathophysiology; preschool child; remission; retrospective study; sex ratio; urinary tract infection; urography; vesicoureteral reflux; Antibiotic Prophylaxis; Child; Child, Preschool; Female; Follow-Up Studies; Humans; Infant; Kidney; Male; Remission, Spontaneous; Retrospective Studies; Severity of Illness Index; Sex Distribution; Urinary Tract Infections; Urography; Vesico-Ureteral Reflux